The Determinants of Corporate Sustainability Performance in Indonesia - Clarissa Delindanoren; Melinda Wijaya (iBuss Management, 2019)
In this past few years, the notion of sustainability has become a prominent matter. In the business context, sustainable development practice is considered imperative due to the reciprocal relationship between business, environment, and society. Sustainability actions are deemed to be beneficial for the company’s competitive advantage, survival, and longevity. Hence, companies nowadays start to incorporate sustainable development in their pursuance, in which this practice is widely recognized as Corporate Sustainability Performance (CSP). Due to its importance, CSP has become an increasingly relevant topic in business and academic world. However, literature that specifically investigates the determinants of CSP is still limited. Thus, this research raises the aforementioned topic to add value and fill the gap of the existing literatures.This research will specifically examine the factors that affect CSP in the context of Indonesia. CSP will be proxied by the persistence inclusion in SRI KEHATI Index. Data of 9 leading CSP firms and 140 non-CSP firms from 2009 until 2017 were collected from Bloomberg Database and Annual Report. The result of the logistic regression indicates that firm size, growth options, and profitability have a significant positive impact on CSP. Meanwhile, leverage and ownership concentration have a significant negative impact on CSP. Keywords:Corporate Sustainability Performance, Size, Profitability, Leverage, Growth Options